KEARIFAN LOKAL PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN DAN PEMBANGUNAN SUMBERDAYA PERIKANAN YANG BERKELANJUTAN (Studi Kabupaten Situbondo) - Syahrul Ibad (Faculty of Science and Technology University Ibrahimy, 2017)
The aim of this research to determine how the local wisdom of community empowerment in the management and sustainable development of fishery resources. This research is using qualitative descriptive approach, which is intended for the careful measurement of specific case studies of social phenomena. Data analysis techniques in this study is using data reduction model, data presentation, and data verification. The result of this research is the local wisdom empowerment of communities in the management and development of fisheries resources. First, local wisdom of ‘Petik Laut’ is happened every year that to give a food of some fish and also to pray in order that the sustainability of fisheries at the sea is maintained. Second, Local Wisdom of ‘Nyabis’ this is done by the local community as the process in order to obtain a blessing that the prayers of the clerics, because the local community is a widespread belief in the presence of this blessing, all the activities from catching, trading and all problems can be more easily and smoothly. Third, Tradition of ‘Tellasan’ in the community on day 27 or H-3, three days before the feast of activities at sea has begun to be stopped, it affects their giving of time on demersal exploited in the arrest for the breed and do regeneration, so the quality and quantity can be properly maintained and continued. In the context of local wisdom in the management of community empowerment and sustainable development of fishery resources required: First, empowerment of local wisdom. Second, management and empowerment model of local communities. Third, build a community-based resource management approaches therein through subjective and structural approach to the measures that can be pursued at the local community by establishing institutions, developing the participation of local communities in decision-making processes, increase a public access for information.